Systematic Review of Interleukin-12, Interleukin-17, and Interleukin-23 Pathway Inhibitors for the Treatment of Moderate-to-Severe Chronic Plaque Psoriasis: Ustekinumab, Briakinumab, Tildrakizumab, Guselkumab, Secukinumab, Ixekizumab, and Brodalumab. Issue 3 (May 2014) - Tausend, William; Downing, Christopher; Tyring, Stephen
Background: Monoclonal antibodies known as biologic agents specifically targeted against interleukin-12 (IL-12), interleukin-17A (IL-17), and interleukin-23 (IL-23) have been the focus of research for moderate-to-severe chronic plaque psoriasis in recent years. Objectives: To discuss the immune-mediated model of psoriasis and to summarize current knowledge of the clinical efficacy and safety of new biologic agents for moderate-to-severe chronic plaque psoriasis. Methods: The PubMed database was searched for relevant articles on ustekinumab, briakinumab, tildrakizumab (MK-322), guselkumab, secukinumab, ixekizumab, and brodalumab published between January 2005 and July 2013. Results: Fifty-five articles were identified. These studies suggest that the biologic agents specifically targeting IL-12, IL-17, and IL-23 are efficacious and safe in the treatment of moderate-to-severe psoriasis in adults. Conclusion: Current data from clinical trials suggest that biologic agents targeting IL-12, IL-17, and IL-23 are safe and efficacious drugs for use in moderate-to-severe chronic plaque psoriasis. Long-term data still need to be established.